Clinical significance and in vitro cellular regulation of hypoxia mimicry on HIF-1α and downstream genes in canine appendicular osteosarcoma. (October 2020) - Gola, C.; Iussich, S.; Noury, S.; Martano, M.; Gattino, F.; Morello, E.; Martignani, E.; Maniscalco, L.; Accornero, P.; Buracco, P.; Aresu, L.; De Maria, R.
Highlights: HIF-1α protein expression correlated with poor prognosis in canine osteosarcomas. CoCl2 -induced HIF-1α stabilisation in canine osteosarcoma cell lines. GLUT-1 transcription was significantly upregulated by hypoxia mimicry. Canine osteosarcoma is an excellent comparative oncology model. Abstract: Cellular adaptation to a hypoxic microenvironment is essential for tumour progression and is largely mediated by HIF-1α and hypoxia-regulated factors, including CXCR4, VEGF-A and GLUT-1. In human osteosarcoma, hypoxia is associated with resistance to chemotherapy as well as with metastasis and poor survival, whereas little is known about its role in canine osteosarcoma (cOSA). This study aimed primarily to evaluate the prognostic value of several known hypoxic markers in cOSA. Immunohistochemical analysis for HIF-1α, CXCR4, VEGF-A and GLUT-1 was performed on 56 appendicular OSA samples; correlations with clinicopathological features and outcome was investigated. The second aim was to investigate the in vitro regulation of markers under chemically induced hypoxia (CoCl2 ). Two primary canine osteosarcoma cell lines were selected, and Western blotting, immunofluorescence and qRT-PCR were used to study protein and gene expression. Dogs with high-grade OSA (35.7%) were more susceptible to the development of metastases ( P = 0.047) and showed high HIF-1α protein expression ( P = 0.007). Moreover, HIF-1α overexpression (56%) was correlated with a shorter disease-free interval (DFI; P = 0.01), indicating that it is a reliable negative prognostic marker. The in vitro experiments identified an accumulation of HIF-1α in cOSA cells after chemically induced hypoxia, leading to a significant increase in GLUT-1 transcript ( P = 0.02). HIF-1α might be a promising prognostic marker, highlighting opportunities for the use of therapeutic strategies targeting the hypoxic microenvironment in cOSA. These results reinforce the role of the dog as a comparative animal model since similar hypoxic mechanisms are reported in human osteosarcoma.